Danger to the Society of Crimes Related to the Transfer of Smuggling Goods Across the Customs Border of the Republic of Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article describes the legal struggle and organizational mechanisms against the transfer of contraband goods across the customs border of the Republic of Uzbekistan. Based on the conducted research, general conclusions were given, and practical recommendations were given to combat the illegal trade of contraband.